2016
DOI: 10.1111/bjet.12440
|View full text |Cite
|
Sign up to set email alerts
|

“I am trying to practice good teaching”: Reconceptualizing eportfolios for professional development in vocational higher education

Abstract: Chris Winberg is the director of the Fundani Centre for Higher Education Development at the Cape Peninsula University of Technology. She holds a South African Research Chair in Work-integrated Learning. The Fundani Centre is responsible for enhancing teaching and learning, and for promoting educational research. Chris' work involves academic and institutional development. Her research focus is professional and vocational education and technical communication. Nicola Pallitt is a lecturer in the Centre for Inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
(11 reference statements)
0
10
0
Order By: Relevance
“…They provide visible and tangible evidence of how students are progressing and allow others to monitor, discuss and assess student learning (Driessen, 2008, p.9). E-portfolios are considered an important tool for student learning and personal development (Joint Information Systems Committee, 2008;Hsieh, Chen & Hung, 2015, p.838), for professional development in vocational higher education (Winberg and Pallitt, 2016;Lim, Lee and Jia, 2016) and for student assessments (Contreras-Higuera, Martinez-Olmo, Rubio-Hurtado & Vila-Banos, 2016;Buyarski & Landis, 2014). Studies such as Attwell (2007), Barrett and Garrett (2009), Meyer et al (2010), Posey et al (2015) and Trevitt, Macduff and Steed (2014) also have shown that positive benefits can be derived from the use of e-portfolios in education both as multimedia containers and as tools to support learning and personal development.…”
Section: E-portfoliosmentioning
confidence: 99%
“…They provide visible and tangible evidence of how students are progressing and allow others to monitor, discuss and assess student learning (Driessen, 2008, p.9). E-portfolios are considered an important tool for student learning and personal development (Joint Information Systems Committee, 2008;Hsieh, Chen & Hung, 2015, p.838), for professional development in vocational higher education (Winberg and Pallitt, 2016;Lim, Lee and Jia, 2016) and for student assessments (Contreras-Higuera, Martinez-Olmo, Rubio-Hurtado & Vila-Banos, 2016;Buyarski & Landis, 2014). Studies such as Attwell (2007), Barrett and Garrett (2009), Meyer et al (2010), Posey et al (2015) and Trevitt, Macduff and Steed (2014) also have shown that positive benefits can be derived from the use of e-portfolios in education both as multimedia containers and as tools to support learning and personal development.…”
Section: E-portfoliosmentioning
confidence: 99%
“…Some are working with postgraduate students to enhance reflection and higher order thinking; and others need to create ePortfolios of their own to demonstrate abilities within their profession and to argue a case for promotion or leadership capabilities (Danowitz, 2012). Winberg and Pallitt (2016) conducted a study with higher education staff working in vocational education to implement ePortfolios. The participants in their study were keen to learn, and valued the possibilities of using an ePortfolio in the future to apply for promotion or teaching awards.…”
Section: Professional Development Needs Of Staffmentioning
confidence: 99%
“…During the professional development sessions and webinars participants were encouraged to create their own ePortfolios, not only to model good practice to students and colleagues, but also to encourage academics, curriculum and educational designers to engage in their own evidence gathering regarding their growth and competency. The interviewees who had created their professional ePortfolios noted the work involved, but acknowledged the resulting value the portfolio had in their career promotions (Winberg & Pallitt, 2016) Expanded purposes of ePortfolio…”
Section: Eportfolio Processes and Products Embedded In Professional Lmentioning
confidence: 99%
“…There exist proposals to support written reflection using digital journals (e.g., Lindroth, 2015), as well as e-portfolios (e.g., Winberg & Pallitt, 2016), with a variety of purposes, from teacher assessment (Lambe, McNair, & Smith, 2013) to the creation of professional learning communities (e.g., shared through social media, Kennedy, 2016).…”
Section: Technological Support For Teacher Reflectionmentioning
confidence: 99%